Globalisation, wage adjustment, and unemployment: An empirical analysis based on the factor price frontier - Dietmar Hornung; Axel Schimmelpfennig; Rüdiger Wapler (Kiel Institute of World Economics (IfW); ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 1997)
We investigate the effects of globalisation on the labour market using the factor price frontier. The factor price frontier defines a negative relationship between the real rate of return and the real wage rate. As international capital mobility equalises the real rate of return in all economies, real wages also have to converge. If they do not adjust, unemployment and technical change will result in relatively capitalabundant countries. We estimate the factor price frontier for the United States and for Germany with the Johansen procedure. While the U. S. economy adjusts along a single factor price frontier throughout the sample, there are three distinct frontiers in the German case. The outward shifts of the factor price frontier coincide with significant hikes in unemployment.
Keywords: E24; F21; 330; Arbeitsmarkt; Faktorpreisausgleich; Standortwettbewerb; Globalisierung; Realzins; Lohn; Arbeitslosigkeit; USA; Deutschland